THE INFLECTIONAL OF PRESEN VERB-INDICATIVE-PARASMAIPADAM THE ROOT OF FIRST CLASS OF VERB SANSKRIT: TRANFORMATION GENERATIVE STUDY - Ni Made Suryati (Balai Bahasa Jawa Barat, 2015)
SANSKRIT language has a very important function for maintaining Hindu religionand Balinese literature. This article aims to find out 1) verbs inventory, 2) theinflectional suffix of present verb-indicative-parasmaipadam the root of first classverb, and 3) to formulate the patterns, using transformational generative theory.The data were taken from dictionaries, books, and Veda. They were collectedusing observation method and note taking and translation techniques. The datawere identified, analyzed using distributional method, continued with patternsand short explanation, and finally explained via tree diagram. The result shows1) there are four verbs inventory, namely person, number, time, and modus; 2)there are nine inflectional suffix of verb present-indicative-parasmaipadam,namely -mi, -vah, -mah, -si, -thah, -tha, -ti, -tah, dan -nti;and 3) there are nine inflectional patterns of verb, namely (1) [x]vI à [x +/-guna a-mi]vpers.I sing., (2) [x]vI à [x +/-guna a-vah]vpers.I dual., (3) [x]vIà [x +/-guna a-mah]vpers.I plur, (4) [x]vI à [x +/-guna a-si]vpers.II sing. (5)[x]vI à [x +/-guna a-thah]vpers.II dual., (6) [x]vI à [x +/-guna a-tha]vpers.IIplur., (7) [x]vI à [x +/-guna a-ti]vpers.III sing., (8) [x]vI à [x +/-guna aah]vpers.III dual., (9) [x]vI à [x +/-guna a-nti]vpers.III plur